Efficacy and safety of direct-acting antivirals in older patients with cirrhosis and high comorbidity index. Issue 3 (March 2020) - Amoros-Reboredo, Patricia; Sotoca, Josep Miquel; Mariño, Zoe; Rodríguez-Tajes, Sergio; Pocurull, Anna; Soy, Dolors; Forns, Xavier; Lens, Sabela
Abstract : Objective: There is scarce data with regard to the effectiveness and safety of direct-acting antivirals and possible drug–drug interactions between antiviral therapy and the multiple drugs frequently assumed by older patients. The aim is to evaluate the impact of comorbidities and drug–drug interactions on the efficacy and tolerability of direct-acting antivirals in this population. Methods: Observational retrospective study of patients at least 65 years old receiving all-oral antiviral therapy between April 2015 and March 2016. Results: Two hundred sixty-one patients were identified. Age distribution: 65–74 (73.9%), 75–79 (18.4%) and ≥80 (7.7%) years. Average age was 71 years, 38.7% were male, and 90% of patients took concomitant medication (43% patients taking ≥ 5 medicines). Predicted clinically significant drug–drug interactions were present in 72.8% of patients. The sustained viral response 12 weeks after end of treatment was 96.9%. Patients with serious adverse events received more concomitant drugs and all of them presented a clinical risk group ≥06/5. Conclusions: Direct antiviral agents are highly effective also in older patients with advanced liver disease, comorbidities and concomitant medications. Serious adverse events increased with the number of concomitant medications and the severity of comorbidity. A clinical risk group score ≥06/5 may help to decide the indication of antiviral therapy in this difficult-to-treat population.